PENGARUH SISTEM INFORMASI AKUNTANSI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN - Indah Ayu Rizky; Novien Rialdy (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this research is to examine and analyze the influence of the Accounting Information System and Human Resource Competence on the Quality of PT's Financial Reports. Herfimta Farm and Plantation. The approach used in this research is an associative approach. The population in this study were all employees of the financial department of PT. Pelindo Belawan Container Terminal has 39 people. The sample in this study used saturated sampling totaling 39 PT people. Herfinta Farm and Plantation. And this research uses survey research with data collection techniques in this research using questionnaire techniques. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that the Accounting Information System influences the Quality of Financial Reports. Human Resource Competency influences the Quality of Financial Reports